Leukotriene B4—leukotriene B4 receptor axis promotes oxazolone‐induced contact dermatitis by directing skin homing of neutrophils and CD8+ T cells. Issue 1 (29th June 2015) - Lv, Jiaoyan; Zou, Linlin; Zhao, Lina; Yang, Wei; Xiong, Yingluo; Li, Bingji; He, Rui
Summary Leukotriene B4 (LTB4) is a lipid mediator that is rapidly generated in inflammatory sites, and its functional receptor, BLT1, is mostly expressed on immune cells. Contact dermatitis is a common inflammatory skin disease characterized by skin oedema and abundant inflammatory infiltrates, primarily including neutrophils and CD8+ T cells. The role of the LTB4–BLT1 axis in contact dermatitis remains largely unknown. In this study, we found up‐regulated gene expression of 5‐lipoxygenase and leukotriene A4 hydrolase, two critical enzymes for LTB4 synthesis, BLT1 and elevated LTB4 levels in skin lesions of oxazolone (OXA)‐induced contact dermatitis. BLT1 deficiency or blockade of LTB4 and BLT1 by the antagonists, bestatin and U‐75302, respectively, in the elicitation phase caused significant decreases in ear swelling and skin‐infiltrating neutrophils and CD8+ T cells, which was accompanied by significantly reduced skin expression of CXCL1, CXCL2, interferon‐γ and interleukin‐1β. Furthermore, neutrophil depletion during the elicitation phase of OXA‐induced contact dermatitis also caused significant decreases in ear swelling and CD8+ T‐cell infiltration accompanied by significantly decreased LTB4 synthesis and gene expression of CXCL2, interferon‐γ and interleukin‐1β. Importantly, subcutaneous injection of exogenous LTB4 restored the skin infiltration of CD8+ T cells in neutrophil‐depleted mice following OXA challenge. Collectively, our results demonstrate that the LTB4–BLT1 axis contributes to OXA‐induced contact dermatitis by mediating skin recruitment of neutrophils, which are a major source of LTB4 that sequentially direct CD8+ T‐cell homing to OXA‐challenged skin. Hence, LTB4 and BLT1 could be potential therapeutic targets for the treatment of contact dermatitis.